2016
DOI: 10.1186/s12879-016-1409-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B infection is highly prevalent among patients presenting with jaundice in Kenya

Abstract: BackgroundViral hepatitis is a major concern worldwide, with hepatitis A (HAV) and E (HEV) viruses showing sporadic outbreaks while hepatitis B (HBV) and C (HCV) viruses are associated with chronic hepatitis, cirrhosis and hepatocellular carcinoma. The present study determined the proportion, geographic distribution and molecular characterization of hepatitis viruses among patients seeking medical services at hospitals throughout Kenya.MethodsPatients presenting with jaundice at four selected hospitals were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 42 publications
(57 reference statements)
10
47
4
1
Order By: Relevance
“…This is consistent with surveys conducted in Rwandan adults and blood donors, which found the majority of HBV infections in Rwanda were due to genotype A. 6,15 In the East African sub-region, HBV infections have been attributed to a genotypes A, B, C, D, E and H, 44,[49][50][51] but HBV genotypes A and D predominate. 11,52 In our study, HCV genotype 4 was the only one identified in confirmed HCV infections, which is consistent with a report on hepatitis care referral patients from Rwanda, in whom 96.7% HCV infections were due to HCV genotype 4.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with surveys conducted in Rwandan adults and blood donors, which found the majority of HBV infections in Rwanda were due to genotype A. 6,15 In the East African sub-region, HBV infections have been attributed to a genotypes A, B, C, D, E and H, 44,[49][50][51] but HBV genotypes A and D predominate. 11,52 In our study, HCV genotype 4 was the only one identified in confirmed HCV infections, which is consistent with a report on hepatitis care referral patients from Rwanda, in whom 96.7% HCV infections were due to HCV genotype 4.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, sporadic rain attributes in water contaminations through pathogens and abiotic mixtures and the water contamination is the major cause of Jaundice occurrence (Raguraman et al, 2017). Similarly, water contamination exacerbates the condition of Hepatitis-B infection (Ochwoto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus genotype A is predominant in South/East Africa, D in North Africa, and E in West/Central Africa [12]. Genotype E hybrids are generally found in African countries with A/E recombinants in Cameroon, Ghana, and Guinea [35, 36] and D/E recombinants in Gabon, Ghana, Niger, Sudan, Kenya, and Ethiopia [33, 35, 37, 38]. There are two documented E hybrids reported from France (A/E) and Ireland (D/E); however, both involve patients originating from Africa [18, 39].…”
Section: Discussionmentioning
confidence: 99%